Akibat Penetrasi Teknologi terhadap Gaya Hidup Masyarakat Desa - Dewi Fatimah; Muta Ali Arauf (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
The penetration of technology in rural communities has brought significant changes in various aspects of life, including social, economic, and cultural dimensions. The presence of digital devices such as smartphones, the internet, and social media has accelerated the flow of information and communication, making it easier for rural residents to access knowledge, business opportunities, and public services. In the economic sector, technology opens new opportunities for small and medium enterprises in villages to market their products more widely through digital platforms. However, these changes also bring challenges, such as shifts in traditional values, increased consumption of potentially unreliable information, and the risk of dependency on technology. Additionally, the digital divide remains an issue, as some rural populations are still unable to optimally utilize technology due to limited infrastructure and digital literacy. This study aims to explore the effects of technology on the lives of rural communities. The research uses qualitative methods, including interviews with village residents and literature review to examine various impacts of technological development in rural life. Findings indicate that technology has opened access to information and new economic opportunities for rural communities. Although technology brings benefits, measures are needed to avoid negative impacts, as demonstrated by the community in Gondangsari Village.